Beaded Coronary Aneurysm in Kawasaki Disease - I-Hsin Tai; Kai-Sheng Hsieh; Ho-Chang Kuo (MDPI AG, 2022)
Kawasaki disease (KD) is a febrile systemic vasculitis that mainly affects children aged under five years old. The aneurysm formation of the coronary artery is the most common complication after KD. We report a case with multiple coronary aneurysm formation and a special pattern ofbeaded aneurysm after KD and review the form ofcoronary aneurysms in different diseases.